A production process of composite film based on UV nano-transfer

CN118952825BActive Publication Date: 2025-01-24LONGKOU KENUOER GLASS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411426088.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-24
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

[0004]然而,随着产品型号的增多,玻璃需求量也在不断的加大,玻璃外观也被固化

Benefits of technology

[0038] 1. The process of preparing the composite film of the present invention is compared to the traditional glass production process. It has the advantages of three -dimensional thickness, rich colors, strong operability, high finished product income, and high work efficiency. The invention is much more convenient for subsequent production changes and derivative products due to the diversity of diaphragms and printed textures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the field of tempered glass technology, and specifically to a production process of a composite film based on UV nano-transfer, comprising the following steps: Step 1: Performing a bottom sealing treatment on the air surface of the tempered glass; Step 2: Using water-based acrylic varnish to screen print on the tin surface of the tempered glass, performing a single-layer primer treatment, and obtaining a first primer layer; Step 3: Bonding a layer of soft film on the first primer layer of the tempered glass, and UV curing to obtain a soft film layer; Step 4: Using water-based acrylic varnish to screen print on the soft film layer again, and after drying, obtaining a second primer layer; Step 5: Performing an embossing treatment on the second primer layer of the tempered glass, and then UV curing again, to obtain the desired composite film. Compared with the traditional glass production process, the process for preparing the composite film of the present invention has the advantages of three-dimensional thickness, rich colors, strong operability, high finished product yield, and high work efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of tempered glass technology, and in particular to a production process of a composite film based on UV nano-transfer. Background Art

[0002] With the advancement of information technology and the development of design aesthetics, smart terminal products such as mobile phones, laptops, and tablets have been deeply integrated and widely penetrated into all aspects of human society. In the new era, product updates and iterations are getting faster and faster. In the situation where performance is gradually becoming excessive, major manufacturers are increasingly inclined to improve the appearance design of products as the key to attracting consumers. Among them, the application of optical texture is to construct micro-nano-level textures to refract, diffuse, diffract or interfere light waves, thereby achieving a variety of rich and cool light and shadow effects.

[0003] UV transfer process is also called UV perfusion process or UV coating process. It uses the non-stick characteristics of UV transfer glue and texture template to transfer various texture effects to PC, PMMA sheets or PET film materials through UV transfer process, so as to produce CD texture, brushed texture, sun texture, batch pattern, woven texture, sandblasted texture, leather texture, 3D surface, fantasy color effect, bulge effect, cat's eye effect, matte surface, glossy surface, high-gloss surface and other effects. It is widely used in ultra-thin buttons, decorative sheets, shells, windows, lenses, LOGO, etc., so that the products have more colorful 2D and 3D appearance texture pattern effects, and are no longer limited to traditional printing, spraying and other 2D effects.

[0004] However, with the increase in product models, the demand for glass is also increasing, and the appearance of glass has been solidified. And with the manufacturers' pursuit of rich light and unique texture, the design and process of optical textures are becoming more and more complicated, and the performance requirements for transfer adhesives are also getting higher and higher. Therefore, this solution provides a composite production process that deeply combines soft film based on UV nano transfer technology with tempered glass and MI process to present an impact appearance process that is completely different from the traditional glass appearance production process. At the same time, the transfer film also has good wear resistance, aging resistance and strength. Summary of the invention

[0005] In view of the problems existing in the prior art, the object of the present invention is to provide a production process of a composite film based on UV nano-transfer.

[0006] The purpose of the present invention is achieved by the following technical solutions:

[0007] A production process of a composite film based on UV nano-transfer printing comprises the following steps:

[0008] Step 1: Perform bottom sealing treatment on the air side of the tempered glass;

[0009] Step 2: Use water-based acrylic varnish to screen print on the tin surface of the tempered glass to perform a single-layer primer treatment to obtain the first primer layer;

[0010] Step 3: Bond a layer of soft film on the first base layer of the tempered glass, and obtain a soft film layer after UV curing;

[0011] Step 4: Use water-based acrylic varnish to screen print on the soft film layer again, and after drying, obtain the second base layer;

[0012] Step 5: The second bottom layer of the tempered glass is embossed and then UV cured again to obtain the desired composite film.

[0013] Preferably, the back cover processing in step 1 includes:

[0014] Platinum ink is printed on the air side of the glass, and then it is baked and cured at 180°C to make the air side of the glass appear metallic.

[0015] Preferably, in step 3, the material of the soft film is any one of PVC, PET, PC, and PE.

[0016] Preferably, in step 4, the drying is performed by baking at 120-130° C. to remove water and dry for 5-10 minutes.

[0017] Preferably, the embossing process in step 5 is an embossing process using a HTMI process on the second base layer.

[0018] Preferably, the UV curing in step 3 and step 5 is performed on a UV curing machine with a wavelength of 365 nm and a radiation amount of 100-200 mW / cm 2 , the curing time is 1-5min.

[0019] Preferably, the water-based acrylic varnish in step 2 and step 4 comprises, calculated in parts by weight:

[0020] 65-85 parts of modified oligomeric acrylic emulsion, 6-12 parts of acrylic acid, 1-2 parts of dispersant, 0.5-0.9 parts of defoamer, 0.03-0.1 parts of photosensitizer, 0.6-1.2 parts of leveling agent, 0.1-0.3 parts of neutralizer and 20-30 parts of deionized water.

[0021] Preferably, the preparation method of the modified oligomeric acrylic acid emulsion comprises:

[0022] S1. Preparation of cross-linked olefin-based POSS:

[0023] Weigh amino cage silsesquioxane (POSS-NH2) and isopropanol, mix them, stir them until they are uniform, then add 3-methyl-2-butenal, then add a catalyst, heat to reflux, keep warm and stir for 4-6 hours, and after the reaction is completed, remove impurities by rotary evaporation to obtain a cross-linked olefin-based POSS;

[0024] S2, preparing pre-reaction solution:

[0025] The cross-linked olefin-based POSS, the first emulsifier and deionized water are mixed, and then acrylic acid, methyl acrylate, butyl acrylate, cyclohexyl acrylate, methacrylic acid and isooctyl methacrylate are added, and stirred for 20-40 minutes to obtain a pre-reaction solution;

[0026] S3, preparing modified oligomeric emulsion:

[0027] The initiator, the second emulsifier and deionized water are mixed, heated to 65-75°C under the protection of nitrogen, and after stirring evenly, the pre-reaction liquid is added dropwise, and the dropping time is controlled to 1 hour. After the dropping is completed, the temperature is raised to 75-85°C, stirred for 1-2 hours, and cooled to room temperature to obtain a modified oligomeric acrylic emulsion.

[0028] Preferably, in S1, the mass ratio of 3-methyl-2-butenal, amino cage-type silsesquioxane and isopropanol is 0.41-0.82:3.6-7.2:50-100.

[0029] Preferably, in S1, the catalyst is triethylamine, and the added amount is 3%-5% of the mass of 3-methyl-2-butenal.

[0030] Preferably, in S2, the mass ratio of the cross-linked olefin-based POSS, acrylic acid, methyl acrylate, butyl acrylate, cyclohexyl acrylate, methacrylic acid, isooctyl methacrylate and deionized water is 0.4-0.8:1-2:0.8-1.4:1.2-1.8:0.2-0.6:0.3-0.8:0.5-1:10-20.

[0031] Preferably, in S2, the first emulsifier is one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium hexadecyl sulfate and sodium hexadecylbenzene sulfonate, and the added amount is 1.5%-2.5% of the mass of the cross-linked olefin-based POSS.

[0032] Preferably, in S3, the mass ratio of the initiator, the second emulsifier, the deionized water and the pre-reaction liquid is 0.05-0.1:4-8:50:50-100.

[0033] Preferably, in S3, the initiator is one of sodium persulfate, potassium persulfate and ammonium persulfate, and the second emulsifier is one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium hexadecyl sulfate and sodium hexadecylbenzene sulfonate.

[0034] Preferably, the dispersant is Digo 760W, the defoamer is BYK-028, the photosensitizer is photosensitizer 1173, the leveling agent is BYK-346, and the neutralizer is ethanolamine.

[0035] Preferably, the preparation method of the water-based acrylic varnish comprises:

[0036] Acrylic acid, dispersant and deionized water are mixed, stirred for 5-10 minutes, and then modified oligomeric acrylic emulsion is added. After stirring for 20-30 minutes, photosensitizer, defoamer, leveling agent and neutralizer are added, and stirred for 5-10 minutes in a dark environment to obtain water-based acrylic varnish.

[0037] The beneficial effects of the present invention are:

[0038] 1. Compared with the traditional glass production process, the process of preparing the composite film of the present invention has the advantages of three-dimensional thickness, rich colors, strong operability, high finished product yield, high work efficiency, etc. Due to the diversity of the film and the embossed texture of the present invention, subsequent production changes and the production of derivative products will be much more convenient.

[0039] 2. The present invention uses a self-made water-based acrylic varnish as a base layer, and uses a modified oligomeric acrylic emulsion as the main raw material, and then completely crosslinks and solidifies after UV light. Compared with conventional varnishes, the varnish prepared by the present invention not only has strong adhesion, but also has better impact resistance, wear resistance and aging resistance.

[0040] 3. Among the components of the water-based acrylic varnish prepared by the present invention, the modified oligomeric acrylic emulsion is obtained by prepolymerization of acrylic monomers and cross-linked olefin-based POSS. Among them, the cross-linked olefin-based POSS is a POSS compound containing olefin groups and Schiff bases prepared by using amino cage-type silsesquioxane (POSS-NH2) and 3-methyl-2-butenal as raw materials through an amine-aldehyde condensation reaction. The cross-linked olefin-based POSS prepared by the present invention is used in the modified oligomeric acrylic emulsion, and compared with conventional olefin-based POSS compounds, the performance of the varnish is greatly improved, mainly in terms of impact resistance, hardness and aging resistance. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is described below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not exclude the existence of other method steps before and after the combination step or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to limit the scope of the present invention. The change or adjustment of the relative relationship thereof shall also be regarded as the scope of the present invention without substantially changing the technical content.

[0042] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0043] The amino cage-type silsesquioxane (POSS-NH2) used in the present invention is aminopropylheptyl-cage-type polysilsesquioxane, and the molecular formula is C 31 H 71 NO 12 The molecular formula of Si8,3-methyl-2-butenal is C5H8O.

[0044] The present invention will be further described below in conjunction with the following examples.

[0045] Example 1

[0046] A production process of a composite film based on UV nano-transfer printing comprises the following steps:

[0047] Step 1: The air side of the tempered glass is sealed with platinum ink, which is then printed on the air side of the tempered glass and then baked and cured at 180°C to give the air side of the glass a metallic color.

[0048] Step 2: Use water-based acrylic varnish to screen print on the tin surface of the tempered glass to perform a single-layer primer treatment to obtain the first primer layer;

[0049] Step 3: Bond a layer of PET soft film on the first base layer of tempered glass and cure it with UV light. The UV curing wavelength is 365nm and the radiation is 150mW / cm 2 , the curing time is 3min, and a soft film layer is obtained;

[0050] Step 4: Use water-based acrylic varnish to screen print on the soft film layer again, bake at 125°C to remove water and dry for 8 minutes to obtain the second base layer;

[0051] Step 5: The second base layer of the tempered glass is embossed with HTMI process and then UV cured again with a wavelength of 365nm and a radiation dose of 150mW / cm 2 , the curing time is 3 minutes, and the desired composite film is obtained.

[0052] The water-based acrylic varnish in step 2 and step 4 is calculated by weight and includes:

[0053] 75 parts of modified oligomeric acrylic emulsion, 8 parts of acrylic acid, 1.5 parts of dispersant Digo 760W, 0.7 parts of defoamer BYK-028, 0.07 parts of photosensitizer 1173, 0.9 parts of leveling agent BYK-346, 0.2 parts of neutralizer ethanolamine and 25 parts of deionized water.

[0054] The preparation method of the modified oligomeric acrylic acid emulsion comprises:

[0055] S1. Preparation of cross-linked olefin-based POSS:

[0056] Weigh amino cage silsesquioxane (POSS-NH2) and isopropanol, mix them, stir them until they are uniform, then add 3-methyl-2-butenal, the mass ratio of 3-methyl-2-butenal, amino cage silsesquioxane and isopropanol is 0.61:5.4:100, then add catalyst triethylamine, the addition amount is 4% of the mass of 3-methyl-2-butenal, heat to reflux, keep stirring for 5 hours, after the reaction is completed, remove the solvent and impurities by rotary evaporation, and obtain cross-linked olefin-based POSS;

[0057] S2, preparing pre-reaction solution:

[0058] The cross-linked olefin-based POSS, sodium lauryl sulfate and deionized water are mixed, and then acrylic acid, methyl acrylate, butyl acrylate, cyclohexyl acrylate, methacrylic acid and isooctyl methacrylate are added, the mass ratio of the cross-linked olefin-based POSS, acrylic acid, methyl acrylate, butyl acrylate, cyclohexyl acrylate, methacrylic acid, isooctyl methacrylate and deionized water is 0.6:1.5:1.1:1.5:0.4:0.5:0.6:15, the addition amount of sodium lauryl sulfate is 2% of the mass of the cross-linked olefin-based POSS, and stirring is carried out for 30 minutes to obtain a pre-reaction solution;

[0059] S3, preparing modified oligomeric emulsion:

[0060] Sodium persulfate, sodium dodecyl sulfate and deionized water were mixed, heated to 70°C under the protection of nitrogen, and stirred evenly. The pre-reaction liquid was added dropwise, the mass ratio of sodium persulfate, sodium dodecyl sulfate, deionized water and pre-reaction liquid was 0.08:6:50:100, and the dropping time was controlled to 1h. After the dropping was completed, the temperature was raised to 80°C, stirred for 1.5h, and cooled to room temperature to obtain a modified oligomeric acrylic emulsion.

[0061] The preparation method of water-based acrylic varnish comprises:

[0062] Acrylic acid, dispersant and deionized water were mixed, stirred for 10 minutes, and then modified oligomeric acrylic emulsion was added. After stirring for 20 minutes, photosensitizer, defoamer, leveling agent and neutralizer were added, and stirred for 10 minutes in the dark to obtain water-based acrylic varnish.

[0063] Example 2

[0064] A production process of a composite film based on UV nano-transfer printing is different from that of Example 1 in that the contents of the aqueous acrylic varnish components in step 2 and step 4 are different.

[0065] The water-based acrylic varnish in step 2 and step 4 is calculated by weight and includes:

[0066] 65 parts of modified oligomeric acrylic emulsion, 6 parts of acrylic acid, 1 part of dispersant Digo 760W, 0.5 parts of defoaming agent BYK-028, 0.03 parts of photosensitizer 1173, 0.6 parts of leveling agent BYK-346, 0.1 parts of neutralizing agent ethanolamine and 20 parts of deionized water.

[0067] The preparation method of the modified oligomeric acrylic acid emulsion comprises:

[0068] S1. Preparation of cross-linked olefin-based POSS:

[0069] Weigh amino cage silsesquioxane (POSS-NH2) and isopropanol, mix them, stir them until they are uniform, then add 3-methyl-2-butenal, the mass ratio of 3-methyl-2-butenal, amino cage silsesquioxane and isopropanol is 0.41:3.6:50, then add catalyst triethylamine, the addition amount is 3% of the mass of 3-methyl-2-butenal, heat to reflux, keep warm and stir for 4 hours, after the reaction is completed, remove impurities by rotary evaporation to obtain cross-linked olefin-based POSS;

[0070] S2, preparing pre-reaction solution:

[0071] The cross-linked olefin-based POSS, sodium dodecylbenzene sulfonate and deionized water are mixed, and then acrylic acid, methyl acrylate, butyl acrylate, cyclohexyl acrylate, methacrylic acid and isooctyl methacrylate are added, the mass ratio of the cross-linked olefin-based POSS, acrylic acid, methyl acrylate, butyl acrylate, cyclohexyl acrylate, methacrylic acid, isooctyl methacrylate and deionized water is 0.4:1:0.8:1.2:0.2:0.3:0.5:10, the addition amount of sodium dodecylbenzene sulfonate is 1.5% of the mass of the cross-linked olefin-based POSS, stirring for 20 min, and obtaining a pre-reaction solution;

[0072] S3, preparing modified oligomeric emulsion:

[0073] Potassium persulfate, sodium dodecylbenzene sulfonate and deionized water were mixed, heated to 65°C under the protection of nitrogen, and stirred evenly. The pre-reaction liquid was added dropwise, and the mass ratio of potassium persulfate, sodium dodecylbenzene sulfonate, deionized water and pre-reaction liquid was 0.05:4:50:50. The dropping time was controlled to 1 hour. After the dropping was completed, the temperature was raised to 75°C, stirred for 1 hour, and cooled to room temperature to obtain a modified oligomeric acrylic emulsion.

[0074] Example 3

[0075] A production process of a composite film based on UV nano-transfer printing is different from that of Example 1 in that the contents of the aqueous acrylic varnish components in step 2 and step 4 are different.

[0076] The water-based acrylic varnish in step 2 and step 4 is calculated by weight and includes:

[0077] 85 parts of modified oligomeric acrylic emulsion, 12 parts of acrylic acid, 2 parts of dispersant Digo 760W, 0.9 parts of defoaming agent BYK-028, 0.1 parts of photosensitizer 1173, 1.2 parts of leveling agent BYK-346, 0.3 parts of neutralizing agent ethanolamine and 30 parts of deionized water.

[0078] The preparation method of the modified oligomeric acrylic acid emulsion comprises:

[0079] S1. Preparation of cross-linked olefin-based POSS:

[0080] Weigh amino cage silsesquioxane (POSS-NH2) and isopropanol, mix them, stir them until they are uniform, then add 3-methyl-2-butenal, the mass ratio of 3-methyl-2-butenal, amino cage silsesquioxane and isopropanol is 0.82:7.2:100, then add catalyst triethylamine, the addition amount is 5% of the mass of 3-methyl-2-butenal, heat to reflux, keep warm and stir for 6 hours, after the reaction is completed, remove impurities by rotary evaporation to obtain cross-linked olefin-based POSS;

[0081] S2, preparing pre-reaction solution:

[0082] The cross-linked olefin-based POSS, sodium hexadecylbenzene sulfonate and deionized water are mixed, and then acrylic acid, methyl acrylate, butyl acrylate, cyclohexyl acrylate, methacrylic acid and isooctyl methacrylate are added, the mass ratio of the cross-linked olefin-based POSS, acrylic acid, methyl acrylate, butyl acrylate, cyclohexyl acrylate, methacrylic acid, isooctyl methacrylate and deionized water is 0.8:2:1.4:1.8:0.6:0.8:1:20, the addition amount of sodium hexadecylbenzene sulfonate is 2.5% of the mass of the cross-linked olefin-based POSS, stirring for 40 minutes, and obtaining a pre-reaction solution;

[0083] S3, preparing modified oligomeric emulsion:

[0084] Ammonium persulfate, sodium hexadecylbenzenesulfonate and deionized water were mixed, heated to 75°C under the protection of nitrogen, and stirred evenly. The pre-reaction liquid was added dropwise. The mass ratio of ammonium persulfate, sodium hexadecylbenzenesulfonate, deionized water and pre-reaction liquid was 0.1:8:50:100. The dropping time was controlled to 1 hour. After the dropping was completed, the temperature was raised to 85°C, stirred for 2 hours, and cooled to room temperature to obtain a modified oligomeric acrylic emulsion.

[0085] Example 4

[0086] A production process of a composite film based on UV nano-transfer, which is different from Example 1 in that the material of the soft film in step 3 is PVC, the baking temperature in step 4 is 120° C., and the baking time is 5 minutes.

[0087] Example 5

[0088] A production process of a composite film based on UV nano-transfer, which is different from Example 1 in that the material of the soft film in step 3 is PC, the baking temperature in step 4 is 130° C., and the baking time is 10 min.

[0089] Comparative Example 1

[0090] A production process of a composite film based on UV nano-transfer printing is different from that of Example 1 in that the contents of the aqueous acrylic varnish components in step 2 and step 4 are different, and other components and methods are the same as those in Example 1.

[0091] Water-based acrylic varnish, calculated by weight, includes:

[0092] 75 parts of oligomeric acrylic emulsion, 8 parts of acrylic acid, 1.5 parts of dispersant Digo 760W, 0.7 parts of defoaming agent BYK-028, 0.07 parts of photosensitizer 1173, 0.9 parts of leveling agent BYK-346, 0.2 parts of neutralizing agent ethanolamine and 25 parts of deionized water.

[0093] The preparation method of the oligomeric acrylic acid emulsion comprises:

[0094] S1. Preparation of pre-reaction solution:

[0095] The cross-linked olefin-based POSS, sodium lauryl sulfate and deionized water are mixed, and then acrylic acid, methyl acrylate, butyl acrylate, cyclohexyl acrylate, methacrylic acid and isooctyl methacrylate are added, the mass ratio of acrylic acid, methyl acrylate, butyl acrylate, cyclohexyl acrylate, methacrylic acid, isooctyl methacrylate and deionized water is 2.1:1.1:1.5:0.4:0.5:0.6:15, the amount of sodium lauryl sulfate added is 2% of the mass of the cross-linked olefin-based POSS, and the mixture is stirred for 30 minutes to obtain a pre-reaction solution;

[0096] S2. Preparation of modified oligomeric emulsion:

[0097] Sodium persulfate, sodium dodecyl sulfate and deionized water were mixed, heated to 70°C under the protection of nitrogen, and stirred evenly. The pre-reaction liquid was added dropwise, the mass ratio of sodium persulfate, sodium dodecyl sulfate, deionized water and pre-reaction liquid was 0.08:6:50:100, and the dropping time was controlled to 1h. After the dropping was completed, the temperature was raised to 80°C, stirred for 1.5h, and cooled to room temperature to obtain a modified oligomeric acrylic emulsion.

[0098] Comparative Example 2

[0099] A production process of a composite film based on UV nano-transfer printing is different from that of Example 1 in that the contents of the aqueous acrylic varnish components in step 2 and step 4 are different, and other components and methods are the same as those in Example 1.

[0100] Water-based acrylic varnish, calculated by weight, includes:

[0101] 75 parts of modified oligomeric acrylic emulsion, 8 parts of acrylic acid, 1.5 parts of dispersant Digo 760W, 0.7 parts of defoamer BYK-028, 0.07 parts of photosensitizer 1173, 0.9 parts of leveling agent BYK-346, 0.2 parts of neutralizer ethanolamine and 25 parts of deionized water.

[0102] The preparation method of the modified oligomeric acrylic acid emulsion comprises:

[0103] S1. Preparation of pre-reaction solution:

[0104] The amino cage silsesquioxane (POSS-NH2), sodium dodecyl sulfate and deionized water are mixed, and then acrylic acid, methyl acrylate, butyl acrylate, cyclohexyl acrylate, methacrylic acid and isooctyl methacrylate are added. The mass ratio of the amino cage silsesquioxane (POSS-NH2), acrylic acid, methyl acrylate, butyl acrylate, cyclohexyl acrylate, methacrylic acid, isooctyl methacrylate and deionized water is 0.6:1.5:1.1:1.5:0.4:0.5:0.6:15, and the amount of sodium dodecyl sulfate added is 2% of the mass of the amino cage silsesquioxane. The mixture is stirred for 30 minutes to obtain a pre-reaction solution.

[0105] S2. Preparation of modified oligomeric emulsion:

[0106] Sodium persulfate, sodium dodecyl sulfate and deionized water were mixed, heated to 70°C under the protection of nitrogen, and stirred evenly. The pre-reaction liquid was added dropwise, the mass ratio of sodium persulfate, sodium dodecyl sulfate, deionized water and pre-reaction liquid was 0.08:6:50:100, and the dropping time was controlled to 1h. After the dropping was completed, the temperature was raised to 80°C, stirred for 1.5h, and cooled to room temperature to obtain a modified oligomeric acrylic emulsion.

[0107] Comparative Example 3

[0108] A production process of a composite film based on UV nano-transfer printing is different from that of Example 1 in that the contents of the aqueous acrylic varnish components in step 2 and step 4 are different, and other components and methods are the same as those in Example 1.

[0109] Water-based acrylic varnish, calculated by weight, includes:

[0110] 75 parts of modified oligomeric acrylic emulsion, 8 parts of acrylic acid, 1.5 parts of dispersant Digo 760W, 0.7 parts of defoamer BYK-028, 0.07 parts of photosensitizer 1173, 0.9 parts of leveling agent BYK-346, 0.2 parts of neutralizer ethanolamine and 25 parts of deionized water.

[0111] The preparation method of the modified oligomeric acrylic acid emulsion comprises:

[0112] S1. Preparation of pre-reaction solution:

[0113] 3-methyl-2-butenal, sodium dodecyl sulfate and deionized water are mixed, and then acrylic acid, methyl acrylate, butyl acrylate, cyclohexyl acrylate, methacrylic acid and isooctyl methacrylate are added, the mass ratio of 3-methyl-2-butenal, acrylic acid, methyl acrylate, butyl acrylate, cyclohexyl acrylate, methacrylic acid, isooctyl methacrylate and deionized water is 0.6:1.5:1.1:1.5:0.4:0.5:0.6:15, the amount of sodium dodecyl sulfate added is 2% of the mass of 3-methyl-2-butenal, and stirring is carried out for 30 minutes to obtain a pre-reaction solution;

[0114] S2. Preparation of modified oligomeric emulsion:

[0115] Sodium persulfate, sodium dodecyl sulfate and deionized water were mixed, heated to 70°C under the protection of nitrogen, and stirred evenly. The pre-reaction liquid was added dropwise, the mass ratio of sodium persulfate, sodium dodecyl sulfate, deionized water and pre-reaction liquid was 0.08:6:50:100, and the dropping time was controlled to 1h. After the dropping was completed, the temperature was raised to 80°C, stirred for 1.5h, and cooled to room temperature to obtain a modified oligomeric acrylic emulsion.

[0116] The performance of the water-based acrylic varnish layer of the composite film based on UV transfer prepared in Example 1 and Comparative Examples 1-3 was tested and compared, including: impact resistance, hardness, adhesion, and aging resistance. The impact resistance test reference standard GB / T 1732-2020, the hardness test reference standard GB / T 6739-2022, the adhesion test reference standard GB / T 9286-2021, and the aging resistance was tested by using a QUV aging instrument UVB-3B lamp for 500 hours to detect the surface gloss retention of the paint film.

[0117] Table 1 Performance test of different varnish layers

[0118]

[0119] It can be seen from Table 1 that the water-based acrylic varnish layer of the composite film based on UV nano-transfer prepared in Example 1 of the present invention has excellent impact resistance, high hardness and adhesion, and also better aging resistance.

[0120] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms should not be understood as necessarily being directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.

[0121] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A production process of a composite film based on UV nanotransfer, characterized in that: The following steps are involved: Step 1: Perform bottom sealing treatment on the air side of the tempered glass; Step 2: Use water-based acrylic varnish to screen print on the tin surface of the tempered glass to perform a single-layer primer treatment to obtain the first primer layer; Step 3: Bond a layer of soft film on the first base layer of the tempered glass, and obtain a soft film layer after UV curing; Step 4: Use water-based acrylic varnish to screen print on the soft film layer again, and after drying, obtain the second base layer; Step 5: The second bottom layer of the tempered glass is embossed and then UV cured again to obtain the desired composite film; Wherein, the water-based acrylic varnish in step 2 and step 4, calculated by weight, comprises: 65-85 parts of modified oligomeric acrylic emulsion, 6-12 parts of acrylic acid, 1-2 parts of dispersant, 0.5-0.9 parts of defoamer, 0.03-0.1 parts of photosensitizer, 0.6-1.2 parts of leveling agent, 0.1-0.3 parts of neutralizer and 20-30 parts of deionized water; The preparation method of the modified oligomeric acrylic acid emulsion comprises: S1. Preparation of cross-linked olefin-based POSS: Weigh the amino cage silsesquioxane and isopropanol, mix them, stir them until they are uniform, then add 3-methyl-2-butenal, then add the catalyst, heat to reflux, keep stirring for 4-6 hours, and after the reaction is completed, remove impurities by rotary evaporation to obtain a cross-linked olefin-based POSS; S2, preparing pre-reaction solution: The cross-linked olefin-based POSS, the first emulsifier and deionized water are mixed, and then acrylic acid, methyl acrylate, butyl acrylate, cyclohexyl acrylate, methacrylic acid and isooctyl methacrylate are added, and stirred for 20-40 minutes to obtain a pre-reaction solution; S3, preparing modified oligomeric emulsion: The initiator, the second emulsifier and deionized water are mixed, heated to 65-75°C under the protection of nitrogen, and after stirring evenly, the pre-reaction liquid is added dropwise, and the dropping time is controlled to 1 hour. After the dropping is completed, the temperature is raised to 75-85°C, stirred for 1-2 hours, and cooled to room temperature to obtain a modified oligomeric acrylic emulsion.

2. The production process of a composite film based on UV nanotransfer according to claim 1, characterized in that: The back cover treatment in step 1 includes: printing on the air surface of the glass using platinum ink, and then performing a 180° C. baking and curing process.

3. The production process of a composite film based on UV nanotransfer according to claim 1, characterized in that: In step 3, the material of the soft film is any one of PVC, PET, PC, and PE.

4. The production process of a composite film based on UV nanotransfer according to claim 1, characterized in that: In step 4, the drying is performed by baking at 120-130° C. to remove water and dry for 5-10 minutes.

5. The production process of a composite film based on UV nanotransfer according to claim 1, characterized in that: The embossing process in step 5 is an embossing process on the second base layer using the HTMI process.

6. The production process of a composite film based on UV nanotransfer according to claim 1, characterized in that: In the S1, the mass ratio of 3-methyl-2-butenal, amino cage-type silsesquioxane and isopropanol is 0.41-0.82:3.6-7.2:50-100; the catalyst is triethylamine, and the added amount is 3%-5% of the mass of 3-methyl-2-butenal.

7. The production process of a composite film based on UV nano-transfer according to claim 1, characterized in that: In S2, the mass ratio of cross-linked olefin-based POSS, acrylic acid, methyl acrylate, butyl acrylate, cyclohexyl acrylate, methacrylic acid, isooctyl methacrylate and deionized water is 0.4-0.8:1-2:0.8-1.4:1.2-1.8:0.2-0.6:0.3-0.8:0.5-1:10-20; the first emulsifier is one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium hexadecyl sulfate and sodium hexadecylbenzene sulfonate, and the added amount is 1.5%-2.5% of the mass of the cross-linked olefin-based POSS.

8. The production process of a composite film based on UV nano-transfer according to claim 1, characterized in that: In S3, the mass ratio of the initiator, the second emulsifier, deionized water and the pre-reaction liquid is 0.05-0.1:4-8:50:50-100; the initiator is one of sodium persulfate, potassium persulfate and ammonium persulfate, and the second emulsifier is one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium hexadecyl sulfate and sodium hexadecylbenzene sulfonate.

9. The production process of a composite film based on UV nano-transfer according to claim 1, characterized in that: The dispersant is Digo 760W, the defoamer is BYK-028, the photosensitizer is photosensitizer 1173, the leveling agent is BYK-346, and the neutralizer is ethanolamine.

Citation Information

Patent Citations

  • Glass production process based on common screen printing

    CN117507650A

  • PET laser holographic film and transfer printing process thereof

    CN117820706A